Relationship Between Knowledge and Perception of Adolescents Aged 15 - 19 Years, and The Stigma of PLWHA in Aesesa Sub-District, Nagekeo District - Florentina Ule; Sigit Purnawan; Indriati A. Tedju Hinga (Media Kesehatan Masyarakat, 2022)
Stigma is considered as a negative social value associated with infected people. Adolescents aged 15 - 19 years are at risk of experiencing sexually transmitted diseases as they are categorized in the age range of being sexually active. This study aims to analyze the relationship between the level of knowledge and perception with stigma perceived by adolescents toward people living with HIV/AIDS or PLWHA. This type of research was an observational study with a cross-sectional design. The research was conducted in Aesesa Sub-district including Tedamude, Tedakisa, Dhawe, Nggolombay, Towak, Nggolonio, Waekokak, Mbay II, Mbay I, Tonggurambang, Marapokot, Danga, Lape, Labolewa, Olaia, Ngegedhawe, Aeramo, and Nangadhero Villages. Data collection was carried out in April - May 2021. The population of this study was 4,122 adolescents aged 15 to 19 years. The sample size was 96 people selected by using simple random sampling. Data were analyzed descriptively and inferentially. Hypothesis testing used chi-square with a significance level of =0.05. The results showed that there was a significant relationship between knowledge and stigma (p=0.003<0.05). Meanwhile, perception was not related to stigma (p-value=0,231>0,05). There is a need for collaboration between educational institutions and the health office in improving reproductive health education, especially related to sexually transmitted diseases.